Redescription of two ghost shrimps (Decapoda: Axiidea: Callianassidae) from the Middle Miocene of the Central Paratethys: systematics, intraspecific variation, and in situ preservation - Hyžný, Matúš; Hudáčková, Natália (Zootaxa, 2012)
A redescription of two Middle Miocene burrowing ghost shrimps of the Central Paratethys, Callianassa brocchiiLőrenthey, 1897 and Callianassa pseudorakosensis Lőrenthey in Lőrenthey & Beurlen, 1929, is provided. Material form-ing the basis of this study comes from the Studienka Formation (lower 'Sarmatian', Serravallian) of the Slovak part of theVienna Basin and exhibits preservation allowing reassignment of the studied taxa to the genera Neocallichirus Sakai, 1988and Eucalliax Manning & Felder, 1991 respectively. The major cheliped of both species exhibits two distinct morphotypesinterpreted herein as possible sexual dimorpism. Several specimens of both taxa are preserved within the tube structuresand are interpreted as in situ preservation within the burrows. Type material of both studied taxa and additional collections from the roughly coeval strata of Hungary and Austria were also studied.